EFEK EKSTRAK DAUN MIMBA LENGKUAS DAN SEREH TERHADAP INFESTASI CAPLAK PADA ANJING - IGK Oka Wirawan; Melkianus Luji Jadi; Bambang Hadisutanto (Partner, 2010)
The Effectiveness of Neem (Azadirachta indica) Leaves Extracts, Galangal, and Lemongrass against brown dog ticks (Riphicephalus sanguineus). The study aimed to find out the effect of herbal extracts (consisted of neem leaf, galangal, and lemongrass) against brown dog ticks by in-vivo. Extracting herbal used cold maceration (Ritiasa, 2000) and clinical trial that was conducted in-vivo to dogs infected by brown dog ticks. The study used a randomized block design, consisting of four treatments, i.e. control and three concentrations of herbal extracts (50%, 75%, and 100%); each treatment was replicated three times. Observed variable was the number of dogs free of brown dog ticks infestation in range of 2 weeks - 2 months (in accordance with the application comaphos). Criteria dogs free of parasites was determined by observing and combing dog hair. The numbers of dogs free of brown dog ticks in each cage were analyzed using one way ANOVA. The results showed that in the first week and second week, herbal extracts do not yet performed a significant influence. This is because the effects pharmacokinetics of herbal extracts that were not exposed to the maximum level. The significant effect of herbal extracts started to happen in the third week, especially on herbal extracts with a concentration of 50%, while, the herbal extract at the concentration of 75% and 100% were not significantly different. In the fourth week, 50% concentration showed more significantly, unrestrained dogs could prove this from brown dog ticks infestation. Keywords: herbal extract, Riphicephalus sanguineus